Subsurface Application Enhances Benefits of Manure Redistribution. Issue 1 (1st February 2016) - Liu, Jian; Kleinman, Peter J. A.; Beegle, Douglas B.; Dell, Curtis J.; Veith, Tamie L.; Saporito, Lou S.; Han, Kun; Pote, Dan H.; Bryant, Ray B.
Abstract : Core Ideas: Manure redistribution adds fertility benefits to recipient fields. Subsurface application of poultry litter has environmental benefits. Redistribution plus subsurface application benefits both farmers and the environment. Sustainable nutrient management requires redistribution of livestock manure from nutrient‐excess areas to nutrient‐deficit areas. Field experiments were conducted to assess agronomic (i.e., corn yield) and environmental (i.e., ammonia volatilization and surface nutrient loss) effects of different poultry litter application methods (surface vs. subsurface) and timings (fall vs. spring) in a potential manure‐importing region in the Chesapeake Bay Watershed in the United States. All four litter treatments (205 kg nitrogen ha −1 ) produced grain yields (10.9–12.8 Mg ha −1 ) nearly equivalent to or higher than the 11.5 Mg ha −1 yield expected from the same mineral nitrogen rate. Compared with surface application, subsurface application significantly reduced ammonia emission ( p < 0.0001), runoff volume (fall: p = 0.02; spring: p = 0.004), and loads of nitrate nitrogen ( p < 0.0001; p = 0.003) and dissolved phosphorus ( p < 0.0001; p = 0.004) soon after application. Integrating subsurface manure application technologies into the manure redistribution programs would help ensure that the surplus nutrients being relocated provide a maximum agronomic impact and minimum environmental impact to the importing region.